EVALUASI KEAMANAN DAM JATILUHUR BERBASIS INDEKS RESIKO - Avazbek Ishbaev; Nora H. Pandjaitan; - Erizal (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
The dams have very important roles to agricultural activities. Especially, West Java with 240,000 hectares of agricultural land, needs a good dam structure that can be used sustainably. Jatiluhur dam in Purwakarta, West Java is one of big dams in Indonesia which has important rules not only for Purwakarta but also for Jakarta, Karawang and Bekasi residents. A study and observation about safety and dam stability is needed to prevent any damage. The purpose of this research were to identify parameters that influenced dam safety and to evaluate dam reliability based on index tools. Analysis was done using risk index tools. The result showed that the condition of the dam of Jatiluhur is still satisfied with indicators, "Idam"-750. The total index risk was 127.22 and the safety factor was 83.04 out of 100. Therefore, Jatiluhur dam could be classified as safe and no need for particular treatments. Jatiluhur dam can be operated in normal condition or abnormal condition with periodic monitoring. Keywords: dam safety, evaluation, Jatiluhur Dam, risk index tools